Determining T- and B- Cell Development by TREC/KREC Analysis in Primary Immunodeficiency Patients and Healthy Controls - (:unkn) unknown (My University, 2021)
T-cell receptor excision circles (TRECs) and kappa-deleting excision circles (KRECs) are DNA fragments potentially indicative of T- and B-cell development, respectively. Recent thymic emigrants (RTEs) are a subset of peripheral cells that may also represent thymic function. Here, we investigated TREC/KREC copy numbers by quantitative real-time PCR in the peripheral blood of patients with primary immunodeficiencies (PIDs, n=145) and that of healthy controls (HCs, n=86) and assessed the correlation between RTEs and TREC copy numbers. We found that TREC copy numbers were significantly lower in children and adults with PIDs (p<0.0001 and p<0.002, respectively) as compared with their respective age-matched HCs. A moderate correlation was observed between TREC copies and RTE numbers among children with PID (r=0.5114, p<0.01), whereas no significant correlation was detected between RTE values and TREC content in the HCs (r=0.0205, p=0.9208). Additionally, we determined TREC and KREC copy numbers in DNA isolated from the Guthrie cards of 200 newborns and showed that this method is applicable to DNA isolated from both peripheral blood samples and dried blood spots, with the two sample types showing comparable TREC and KREC values. We further showed that RTE values are not always reliable markers of T-cell output. Although additional confirmatory studies with larger cohorts are needed, our results provide thresholds for TREC/KREC copy numbers for different age groups.
Keywords: Primary immune deficiency; Newborn screening; KREC (kappa-deleting excision circle); Recent thymic emigrants (RTEs); TREC (T-cell receptor excision circle)